2014
DOI: 10.1088/0967-3334/36/1/67
|View full text |Cite
|
Sign up to set email alerts
|

Performance limits of ICA-based heart rate identification techniques in imaging photoplethysmography

Abstract: Imaging photoplethysmography is a relatively new technique for extracting biometric information from video images of faces. This is useful in non-invasive monitoring of patients including neonates or the aged, with respect to sudden infant death syndrome, sleep apnoea, pulmonary disease, physical or mental stress and other cardio-vascular conditions. In this paper, we investigate the limits of detection of the heart rate (HR) while reducing the video quality. We compare the performance of three independent com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…Efforts in the area of image processing have been focused on targeted region of interest (ROI) selection 37 , color manipulations to achieve chrominance-based iPPG 38 , and motion artifact reduction 9,39,40 . In the area of signal processing, methods for detecting individual pulse waves 41,42 and blind source separation (BSS), particularly Independent Component Analysis (ICA) 7,8,43,44 and Principle Component Analysis (PCA) 45 for recovering an iPPG signal. Further efforts have been devoted toward modified collection methods including using an imager with additional color bands (red, green, blue, cyan, orange) to increase channel space inputs for blind source separation 15,46 or using near infrared light sources and a near infrared imager to successfully collect iPPG signals when highly variable, visible lighting conditions exist 47 .…”
Section: Introductionmentioning
confidence: 99%
“…Efforts in the area of image processing have been focused on targeted region of interest (ROI) selection 37 , color manipulations to achieve chrominance-based iPPG 38 , and motion artifact reduction 9,39,40 . In the area of signal processing, methods for detecting individual pulse waves 41,42 and blind source separation (BSS), particularly Independent Component Analysis (ICA) 7,8,43,44 and Principle Component Analysis (PCA) 45 for recovering an iPPG signal. Further efforts have been devoted toward modified collection methods including using an imager with additional color bands (red, green, blue, cyan, orange) to increase channel space inputs for blind source separation 15,46 or using near infrared light sources and a near infrared imager to successfully collect iPPG signals when highly variable, visible lighting conditions exist 47 .…”
Section: Introductionmentioning
confidence: 99%
“…pulse). The study of cardio-vascular pulse waves traveling through the body and the monitoring of blood flow and its velocity, provide indications in the diagnostic of vascular disease [41], but also can help in the monitoring of conditions related to sudden infant death syndrome, sleep apnoea or pulmonary disease [42]. While different methods have been developed in the past to detect pulse [43], alternative non-contact solutions based on photoplethysmography or thermal imaging, able to capture the pulsatile peripheral blood flow, have been promoted.…”
Section: A Monitoring Of Vascular Pulsementioning
confidence: 99%
“…FastICA, RADICAL) gave better results than other (JADE, Robust ICA) [4,5]. However, in [5] the authors showed that sometimes there were problems with ICA algorithms, for example, FastICA failed to properly initialize. It was also shown that using a camera embedded in a laptop computer the use of green trace, bypassing the ICA stage, gave better results.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that some algorithms (i.e. FastICA, RADICAL) gave better results than other (JADE, Robust ICA) [4,5]. However, in [5] the authors showed that sometimes there were problems with ICA algorithms, for example, FastICA failed to properly initialize.…”
Section: Introductionmentioning
confidence: 99%